IMPROVING THE STUDENTS’ SPEAKING ABILITY THROUGH ZOOM APPLICATON AT POTENSI UTAMA UNIVERSITY - Reni Rosianna Lumbangaol (Universitas Potensi Utama, 2021)
Regarding the worldwide use of virtual applications in the EFL teaching and learning process, there were a lot of obstacles and limitations. In developed countries as the USA, Europe, etc, they were able to manage how to use virtual application very successfully in teaching and learning process. Even though, the improvement of using each virtual application still needs more researches for specific applications’ effect. In this research, the writer used the zoom application as a tool to examine the effect on students speaking ability. The research consisted of 20 English students at Potensi Utama University. They were tested to know theirs speaking ability in scores and taught speaking material through zoom application. The zoom application was used in teaching the students of the third semester of the academic year (2020-2021). Data were collected from the study participants using an oral speaking test, an attitudinal questionnaire, and Semi-structured interviews. The results indicated that there was a significant improvement of students after studying using the zoom application. The progress of speaking ability is significantly found in fluency, pronunciation, grammar, comprehension, and vocabulary due to the virtual classes. However, using the zoom application could satisfy the lecturer and students. It showed the average scores of the Pre-Test were 49,1, Post Test-1 was 69,2 and Post-Test II was 90,7. There were a significant improvement from Pre to Post Test I and a higher figure at Post Test II. The questionnaire and interview findings also revealed that students generally had positive attitudes towards using zoom application as virtual classes particularly because they found it helpful and efficient in improving their speaking ability. In those findings, the researcher suggested using zoom application could be a favorite teaching method in the mids of the pandemic to increase students’ speaking ability. The words: EFL (English as Foreign Language), Zoom Application, Speaking Ability